2022
DOI: 10.1021/acscatal.2c02230
|View full text |Cite
|
Sign up to set email alerts
|

Size and Coverage Effects of Ni and Pt Co-Catalysts in the Photocatalytic Hydrogen Evolution from Methanol on TiO2(110)

Abstract: In the past decade, hydrogen evolution from photocatalytic alcohol oxidation on metal-loaded TiO2 has emerged as an active research field. While the presence of a metal cluster co-catalyst is crucial as a H2 recombination center, size and coverage effects on the catalyst performance are not yet comprehensively understood. To some extent, this is due to the fact that common deposition methods do not allow for an independent change in size and coverage, which can be overcome by the use of cluster sources and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Many researchers have reported that noble metal NPs, such as Au, Pt, Ag, Rh, Ni-Pt, Pd, Cu-Pd, and Au-Pd have been reported resulting in enhanced overall photocatalytic activity by enhancing the electron-hole charge separation. [61][62][63][64][65][66][67][68][69][70][71] In this regard, SnS 2 nanostructures were synthesized by hydrothermal method and were in situ decorated with Ni as a cocatalyst having different concentrations of Ni i.e., 1 mol%, 2.5 mol%, 5 mol%, and 10 mol% through a simple thermal reduction method. The detailed physico-chemical characterisation and inuence of Ni loading on SnS 2 towards its photocatalytic performance were investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have reported that noble metal NPs, such as Au, Pt, Ag, Rh, Ni-Pt, Pd, Cu-Pd, and Au-Pd have been reported resulting in enhanced overall photocatalytic activity by enhancing the electron-hole charge separation. [61][62][63][64][65][66][67][68][69][70][71] In this regard, SnS 2 nanostructures were synthesized by hydrothermal method and were in situ decorated with Ni as a cocatalyst having different concentrations of Ni i.e., 1 mol%, 2.5 mol%, 5 mol%, and 10 mol% through a simple thermal reduction method. The detailed physico-chemical characterisation and inuence of Ni loading on SnS 2 towards its photocatalytic performance were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have reported that noble metal NPs, such as Au, Pt, Ag, Rh, Ni-Pt, Pd, Cu-Pd, and Au-Pd have been reported resulting in enhanced overall photocatalytic activity by enhancing the electron–hole charge separation. 61–71…”
Section: Introductionmentioning
confidence: 99%
“…[17] Finally, in a recent non-electrochemical study, specific Pt clusters (most notably Pt 10 ) on titania (TiO 2 ) were reported to show high and stable catalytic activity toward the photo-induced production of H 2 compared to Pt 1 /TiO 2 . [18] Herein, we present a joint experimental and theoretical study of the activity and stability of size-selected Pt 1,4,7,8 clusters deposited fluorine-doped tin oxide (FTO) electrode supports, towards the electrocatalytic hydrogen evolution reaction (HER). Mass-selected deposition in ultra-high vacuum (UHV) was used to prepare electrodes with identical Pt loadings, differing only in cluster size.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Finally, in a recent non-electrochemical study, specific Pt clusters (most notably Pt10) on titania (TiO2) were reported to show high and stable catalytic activity toward the photo-induced production of H2 compared to Pt1/TiO2. [18] Herein, we present a joint experimental and theoretical study of the activity and stability of size-selected Pt1,4,7,8 clusters deposited fluorine-doped tin oxide (FTO) electrode supports, towards the electrocatalytic hydrogen evolution reaction (HER). Mass-selected deposition in ultra-high vacuum (UHV) was used to prepare electrodes with identical Pt loadings, differing only in the size of clusters deposited.…”
Section: Introductionmentioning
confidence: 99%